Prevalence of Musculoskeletal Problems and Its Impact on the Health-Related Quality of Life Among the Cricketers - Smrutimeera Sahoo; Khamer Anisa Fathima (International Journal of Allied Medical Sciences and Clinical Research, 2023)
Cricket is that the hottest sport in India far and away, and is played almost everywhere. It is increasingly demanding sports, so require skilled movement and physical fitness. The continuous changing posture of the bats man are causing the complications like pain and discomfort affecting the day to day functions, so as quality of life. A necessity was felt to assess the health status and quality of life of the cricketers for which Occupational Therapy treatment can be implemented to overcome the physical discomfort and to give better quality of life. This study aims to determine the prevalence of musculoskeletal problems and its impact on physical and mental health-related quality of life among the cricketers. The study included a quantitative cross-sectional design which was conducted among the male cricketers sampling from different cricket and cricket club in Tamilnadu. Modified Nordic Musculoskeletal Questionnaire was used to determine the prevalence of musculoskeletal problems and RAND 36-Item Health Survey 1.0 Questionnaire was used to determine the impact of musculoskeletal problems on the physical and mental health- related Quality of Life. Based on convenience sampling 50 male cricket players were included with age range of 18-33 years and the study results concluded that, out of 50 participants 48 (96%) of the population have trouble in last 12 months (such as musculoskeletal ache, pain, discomfort, numbness) in different parts of body. The Physical composite score and Mental composite score mean was 39.95 and 49.58 respectively which associated with a lower health-related quality of life among cricket players specifically in the domains of physical functioning, physical health, bodily pain as well as emotional problems and energy/fatigue resulted in considerably lower HRQoL. The relationship impact of variables having trouble in last 12 months, showed a p-value for variables of shoulder (p = 0.00526) and wrists/hands (p = 8.4e-06) were significant in impacting the PCS and the p-value for variable Wrists/Hands (p = 0.0439) was significant in impacting MCS. Similarly, the correlation impact variables of having trouble in last 12 months of being prevented from carrying out the normal activities, showed a p-value for variables of shoulder (p = 0.000362) and wrists/hands (p = 0.002213) were significant in impacting the PCS. This study concluded that male cricketers have a high level of prevalence of musculoskeletal problems especially in shoulder, wrists/hands and neck followed by the lower extremity and these high prevalence (i.e., variables of shoulders, wrists/hands and neck) musculoskeletal problems have significant impact in their physical (PCS) and mental (MCS) health-related quality of life.